Stokes drift: theory and experiments. (10th February 2020) - Monismith, Stephen G.
Abstract : Abstract : An important facet of water wave dynamics is the fact that Stokes' 1847 approximate theory of water waves predicts mean Lagrangian velocities even when mean Eulerian velocities are zero. This motion, known as Stokes drift, is important to a wide variety of oceanic processes. Reflecting the difficulty of avoiding effects associated with the boundaries in wave tanks, the first convincing experimental evidence confirming this behaviour has only recently been given in van den Bremer et al. ( J. Fluid Mech., vol. 879, 2019, pp. 168–186). This is an important result given prior evidence that the exact rotational waves first studied by Gerstner in 1802 may exist. Nonetheless, despite more than 200 years of work on the theory of water waves, much remains to be discovered.